PENGGUNAAN VIRTUAL REALITY PADA PASIEN DI RUANG INTENSIVE CARE UNIT (ICU) : SEBUAH TINJAUAN LITERATUR: VIRTUAL REALITY IN INTENSIVE CARE UNIT : A LITERATURE REVIEW - Khairunisa, Prima; Herawati, Tuti (BIMIKI (Berkala Ilmiah Mahasiswa Ilmu Keperawatan Indonesia), 2023)
Background: In addition to physical issues, the critical condition that the ICU patients experience also causes a psychological impact that lasts until they leave the ICU treatment. Virtual reality is one of the latest innovations utilized to support the treatment in the ICU. Virtual reality is one of the supporting tools in non-pharmacology interventions to reduce anxiety, stress, and sleep deprivation, as well as mitigate post-traumatic disorder syndrome or PTSD. The research aims to describe the framework for utilizing virtual reality to reduce anxiety, stress, and sleep deprivation, as well as mitigate post-traumatic disorder syndrome. As well as to see how feasible it is to utilize this technology from the security and usage tolerance perspective. Method: The methode was a literature review. The author search the articles on Google Scholar by filtering search results based on the publication year, article title, and abstract. The research resulted in ten articles to be the literature review. Result: The search result found ten articles discussing virtual reality on ICU patients as an intervention to reduce anxiety, pain, and sleep deprivation. The research also found that it is feasible to use Virtual reality as an intervention media. From the safety perspective, the technology is safe due to being regularly disinfected and not affecting other life-support tools that the patients need. It also has minimum side effects during usage. Conclusion: Virtual reality is effective in reducing anxiety, pain, and sleep deprivation in ICU patients. From the safety viewpoint and usage tolerance, the technology is safe and feasible for ICU patients.